2013
DOI: 10.2460/ajvr.74.5.733
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive measurements of body composition and body water via quantitative magnetic resonance, deuterium water, and dual-energy x-ray absorptiometry in awake and sedated dogs

Abstract: QMR was useful for determining body composition in dogs and can be used to safely and rapidly acquire accurate data without the need for sedation or anesthesia. These benefits can facilitate frequent scans, particularly in geriatric, extremely young, or ill pets. Compared with the D2O dilution method, QMR correction equations provided accurate assessment over a range of body compositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…8,[17][18][19][20] However, several studies also showed that QMR underestimated FM when using deuterium dilution and a fourcomponent model as the gold standard. [21][22][23][24][25][26] Values for both FM and FFM, while significantly different from CCA values, were still significantly correlated for each body compartment measure. For FFM, residual bias increased significantly with increasing CCA mass, while residual bias did not occur for FM.…”
Section: Discussionmentioning
confidence: 81%
“…8,[17][18][19][20] However, several studies also showed that QMR underestimated FM when using deuterium dilution and a fourcomponent model as the gold standard. [21][22][23][24][25][26] Values for both FM and FFM, while significantly different from CCA values, were still significantly correlated for each body compartment measure. For FFM, residual bias increased significantly with increasing CCA mass, while residual bias did not occur for FM.…”
Section: Discussionmentioning
confidence: 81%
“…However, the deuterium dilution technique is a lengthy and costly process that requires animals to be anesthetized, the collection of several blood samples, and expensive equipment that is rarely found in general veterinary practices, which makes it impractical in most situations. Isotopic dilution is most useful for validation of alternative techniques for evaluation of body composition, such as DEXA 13,14 or quantitative MRI. 14 A 9-point scale has been proposed for assessment of the body condition of dogs that involves observation and palpation of the animal to evaluate the percentage of body fat.…”
Section: Bcsmentioning
confidence: 99%
“…In the dogs, we were unable to obtain information regarding the volume of the adipose tissues. However, the body fat mass of beagle dogs, which includes not only the adipose tissues but also the lipid content in blood and other tissues, has been reported and the body fat percentage could be calculated as about 17-20 % [11]. Therefore, we assumed that 15 % of the body weight was related to the adipose tissue volume in dogs.…”
Section: Discussionmentioning
confidence: 99%